2011
DOI: 10.1093/ejechocard/jer058
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of left atrial volume index in patents with first acute myocardial infarction

Abstract: AimsWe evaluated the usefulness of left atrial volume index (LAVI) and the degree of changes in LAVI (delta LAVI) during hospitalization for the prediction of prognosis after acute myocardial infarction (AMI). Methods and resultsWe investigated 205 consecutive patients with first AMI. They underwent echocardiography on admission as well as at discharge. Delta LAVI was calculated by subtracting the value on admission from that at discharge. The primary endpoints were major cardiac events (MACE): cardiac death d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…LAVI is as well as an important marker in the development of atrial fibrillation and seems to be an important parameter in predicting atrial fibrillation. The importance of LAVI, it has been used in atrial fibrillation, for monitoring of the success of electrical cardioversion and the formation of and recurrence, the results of mitral balloon valvuloplasty, and prognosis of acute myocardial infarction and development of major cardiac event, and to predict AF recurrences after radiofrequency ablation and it has been shown that, increased LAVI values were associated with poor prognosis 6,18,19,20 . However, in these studies, the cut off value of LAVI for AF has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAVI is as well as an important marker in the development of atrial fibrillation and seems to be an important parameter in predicting atrial fibrillation. The importance of LAVI, it has been used in atrial fibrillation, for monitoring of the success of electrical cardioversion and the formation of and recurrence, the results of mitral balloon valvuloplasty, and prognosis of acute myocardial infarction and development of major cardiac event, and to predict AF recurrences after radiofrequency ablation and it has been shown that, increased LAVI values were associated with poor prognosis 6,18,19,20 . However, in these studies, the cut off value of LAVI for AF has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of mitral stenosis is preparing ground for the formation of atrial fibrillation. Left atrial pressure increase caused by long-term mechanical obstruction is preparing ground for the development of atrial fibrillation 10,11,20 . In parallel to these findings in our study, we determined that the average age of patients with AF was more.…”
Section: Discussionmentioning
confidence: 99%
“…В противоположность этому объём левого предсердия (ЛП) менее зависим от острых гемодинамических изменений и отражает подострую или хроническую диастолическую дис-функцию. Прогностическое значение размера и объ-ёма ЛП после ИМ изучалось в нескольких исследова-ниях [28][29][30].…”
Section: прогностическая значимость эхокардиографии после острого инфunclassified
“…LA also reflects LV filling pressure and is capable of remodeling (enlarging) in response to its elevation [1, 2]. Although there is a growing body of evidence demonstrating that LA enlargement is an independent marker of adverse outcomes both in primary [37] and secondary [811] cardiovascular prevention, to date, there are no published data assessing long-term outcome in patients undergoing valve and coronary artery by-pass graft (CABG) surgery.…”
Section: Introductionmentioning
confidence: 99%